The Trouble with Five: New Synthetic Strategies toward C5-Symmetric Pillar[5]arenes and Beyond - Du, Ke; Sue, Andrew C.-H. (Synlett, 2019)
Rim-differentiated pillar[5]arenes (P[5]s) are intriguing macrocyclic molecular platforms with C5-symmetry, but their conventional statistical syntheses suffer from low yields and laborious separation. Our group recently reported a ‘pre-oriented’ protocol that results in highly selective production of C5-symmetric P[5]s among four constitutional isomers. Subsequently, we devised a more general divergent synthetic route starting with a common P[5] precursor with rim differentiation, followed by a series of high-yielding reactions that permit successive transformations of both rims freely. As a result, a variety of rim-differentiated P[5]s can be made to order in gram-scale quantities. This total solution not only populates the list of C5-symmetric P[5]s, but also enables further design and synthesis of assorted five-fold organic building blocks towards complex supramolecular architectures.
Keywords: five-fold symmetry; C5-axis; pillar[5]arenes; rim differentiation; regioselectivity; macrocycles